Sustainable Supply Chain Management: Factor Analysis - Nurul Fadly Habidin; Aqmar Nur Izzah Norazlan; Nursyazwani Mohd Fuzi (International Journal of Supply Chain Management, 2019)
The purpose of this study is to identify the sustainable supply chain management (SSCM) by using factor analysis (exploratory factor analysis and confirmatory factor analysis). Using a survey questionnaire, data were collected 230 respondents from private hospitals in Malaysia. The findings found that the factor analysis for SSCM model was fit and acceptable with four dimensions (environment, information and communications technology, culture change, and risk management). Regarding this, SSCM model provides a useful guide for Malaysian private hospitals to implement supply chain in terms of SSCM dimensions. Thus, SSCM practices implementation can improve the supply chain and performance in Malaysian private hospitals.